Resurfacing the Submerged Past Prehistoric Archaeology and Landscapes of the Flevoland Polders, the Netherlands. - Peeters, Hans (Sidestone Press, 2021)
The Netherlands are internationally renowned for the archaeology of its wetland environments. The reclamation of the Flevoland Polders in the early half of the 20th century not only exposed hundreds of shipwrecks, but also remnants of prehistoric landscapes and traces of human occupation dating to Mesolithic and Neolithic times. Ultimately, this led to the 'discovery' of the Swifterbant Culture in the 1960s-1970s, and which was initially seen as a Dutch equiva.